Reproduction and maternal care increase oxidative stress in a mouthbrooding cichlid fish. (16th August 2019) - Sawecki, Jacob; Miros, Emily; Border, Shana E; Dijkstra, Peter D
Abstract: Investment in reproduction and postzygotic parental care is an energetically costly yet fundamental aspect of the life-history strategies in many species. Recently, oxidative stress has received attention as a potential mediator in the trade-off between reproduction, growth, and survival. During activities that increase metabolic activity, such as providing offspring care, an overproduction of reactive oxygen species can occur that cannot be counteracted by antioxidants, leading to oxidative stress and tissue damage. Here, we investigated the oxidative costs of reproduction and maternal care over the course of the reproductive cycle in a mouthbrooding cichlid fish within socially stable and unstable environments. We manipulated social stability by disrupting the habitat in socially unstable tanks. We expected to see an increase in the burden of maternal care within unstable environments due to increased male harassment of females as a byproduct of increased male–male aggression. We found that brooding females have higher levels of oxidative stress than nonbrooding females and oxidative stress fluctuates throughout the reproductive cycle. These fluctuations were driven by a spike in reactive oxygen metabolites at the beginning of brood care followed by an increase in antioxidant defense. Surprisingly, the link between reproduction and oxidative stress was not different between females from stable or unstable environments. Our study illustrates a more complete picture of the physiological costs of reproduction and parental care throughout different stages of care rather than a simplistic end-point observation of how reproduction and parental care affect an individual. Abstract : The decision to provide care for offspring over investment in self-maintenance can be challenging. Within a cichlid fish species, mothers care for offspring within their mouths for upward of 2 weeks. Offspring benefit from reduced mortality and increased fitness, but mothers acquire the burden of reduced body condition and oxidative stress, which could lead to tissue damage.